Cultural energy analyses of climatologically suitable places in Turkey for feedlot cattle production determined by using the comprehensive climate index model - Koknaroglu, H.; Harrington Jr, John; Mader, T. L. (My University, 2016)
The objective of this study was to conduct cultural energy analyses on feedlot cattle production in Turkey. The comprehensive climate index (CCI) model was used to predict DMI, ADG, and feed efficiency of feedlot cattle in 15 locations in Turkey. The CCI enables one to quantify beef cattle performance for a number of breeds based on environmental conditions (temperature, relative humidity, wind speed, and solar radiation) at any time in the year. Because mostly dairy breed calves are placed into the feedlot in Turkey, the Holstein (dairy breed) option in the CCI was chosen to calculate the maintenance energy requirement. Based on previous feedlot feeding studies conducted in Turkey, it was assumed that calves would be placed on feed at 250 kg and be marketed at 520 kg and that the diet would have 2600 kcal/kg metabolic energy and would have DMI of 2.31% of the BW. It was assumed that cattle would receive 2 kg/d straw and that the concentrate mixture would consist of 52.65% barley, 26% corn, 19% cotton seed meal, 1.5% limestone, 0.25% vitamins, 0.5% salt, and 0.1% minerals. Cultural energy inputs were calculated by multiplying the amount of inputs and their corresponding cultural energy based on values from existing literature. Cultural energy used for feed was derived from DMI of cattle and corresponding values for each feed ingredient. Transportation energy was also included in the analysis, including costs for shipping calves from animal market to the farm, shipping yearlings to slaughterhouse, and shipping feed ingredients to the farm. Cultural energy expended for feed made up more than half of the total cultural energy and differed among cities (P < 0.05). Cultural energy for feed was highest for the coldest places and lowest for hot locations. Cultural energy of transportation constituted the second highest cultural energy expenditure. Cultural energy expended per kilogram live weight gain (defined as total cultural energy expended divided by kg live weight gain) was highest for the coldest location and lowest for relatively hotter cities (P < 0.05). Cultural energy use efficiency (defined by kcal input/kcal output) followed the feed efficiency ranking with cattle having better feed efficiency also have better cultural energy use efficiency. Results showed that cattle having higher ADG did not mean that they would also have better cultural energy use efficiency.
Citation: Koknaroglu, H., Harrington, J. A., & Mader, T. L. (2016). Cultural energy analyses of climatologically suitable places in Turkey for feedlot cattle production determined by using the comprehensive climate index model. Journal of Animal Science, 94, 26-26. doi:10.2527/msasas2016-057
Keywords: Beef Cattle; Comprehensive Climate Index; Cultural Energy; Feedlot; Agriculture